Avaliação do potencial antibacteriano e antibiofilme do líquido da casca da castanha de caju sobre bactérias orais - Souza, Nayara de Oliveira (2020)
Dental caries is the most prevalent disease of the oral cavity. In addition to other etiological factors, the disease is developed by the presence of biofilms responsible for demineralization of dental hard tissues. Currently, there is a growing interest in the literature for products of natural origin as a source of new bioactive substances for dental biofilm control. Cashew nut shell liquid (CNSL) is considered as an agribusiness residue and research has shown its potential for the development of functional products in the medical field. Thus, the objective of this study was to evaluate the antimicrobial and antibiofilm potential of the natural and technical (obtained after the nut roasting process) CNSL against oral bacteria. For this purpose, the assays were performed in planktonic cells culture and biofilm, using the following strains: Streptococcus sobrinus ATCC 6715, Streptococcus oralis ATCC 10557, Streptococcus mutans UA (159), Streptococcus parasanguinis ATCC 903 and Enterococcus faecalis ATCC 19433. For planktonic cell tests, the strains were subjected to the technique of microdilution to perform the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (CBM) assays. For biofilm assays were analyzed the biomass quantification and the counting of colony forming units (CFU) for both biofilm inhibition and preformed biofilm tests. The BHI (Brain Heart Infusion) medium containing the adjusted bacterial suspension was used as a negative control. The results were analyzed by one-way ANOVA and Bonferroni post-test (p<0.05). The antibacterial effect on planktonic cells, the CNSLs, technical and natural, showed activity for all strains tested, with MIC and CBM values ranging from 1.5 to 25 μg ml-1. For biofilm assays, the CNSLs, technical and natural, showed reduction of biomass and CFU number for all bacteria, except for S. parasanguinis treated with technical LCC. In preformed biofilms, there was also a reduction in biomass and CFU number for all strains, except for S. oralis treated with technical CNSL. In conclusion, both substances showed effective antibacterial and antibiofilm activity against oral bacterial used in the study, however in general, natural CNSL showed better results compared to technical CNSL.